LANGUAGE FORMALITY ON TV PROGRAM 'SATU INDONESIA' - Simanjuntak, Pebruarika Nova; Hasibuan, Juli Rachmadani; Putri, Citra Anggia (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
This study deals with Language Formality used on TV program 'Satu Indonesia Net TV'. The objectives of this study were to find out the level of the language and describe the language formality in  TV  program. This  research  was  conducted  by  using descriptive qualitative Method. The data were the dialogues in program 'Satu Indonesia' special  episode  August  12th   2016 and  17th   December  2016  which  was  taken  from YouTube. The findings indicated that there were four level of formalities found on Program Satu Indonesia. There were 4,87% Frozen,31% Formal, Consultative 21,95 and 18,85% Casual. The most dominant level that is used by the figures in this program was Formal Level. It explained that, the figures from political scale used the language differently based on the context and the situation that is held in a conversation.